Application of 3D-AIR Media on Lithosphere Material for Class X Students at Senior High School 8 Banjarmasin - Nevy Farista Aristin; Karunia Puji Hastuti; Deasy Arisanty; Muhammad Muhaimin (Universitas Lambung Mangkurat, 2026)
This study aims to evaluate the effectiveness of 3D-AIR media in enhancing students' geography learning outcomes at SMA Negeri 8 Banjarmasin. This type of research uses an experimental design with a nonequivalent pretest-posttest control group design. The sample for this study consisted of students in class X.5 (experimental) and X.6 (control) in the 2024/2025 academic year. The experimental class received treatment with 3D-AIR media, while the control class did not use any learning media. The material taught in this study was the lithosphere. The data collection technique used a multiple-choice test. The data were analyzed using the Mann-Whitney test, which showed that the Asymp. Sig. (2-tailed) of 0.861 > 0.05 indicates that there is no increase in geography learning outcomes through 3D-AIR media in class X students at SMA Negeri 8 Banjarmasin. This is due to various learning component factors, including 3D-AIR media and supporting facilities used during classroom learning. 3D-AIR media still has shortcomings, namely that it is only compatible with Android-based devices. However, some students use iOS and HarmonyOS-based devices, which can hinder their access to lithosphere materials during learning. Furthermore, Wi-Fi network support in the school environment remains suboptimal, limiting the use of 3D-AIR media in learning. Therefore, research findings on supporting facilities for the application of 3D-AIR media in lithosphere learning are the main focus, to optimize student activities and the quality of geography learning in the technology era.